PROTOCOL: the On Track 2.0 cluster randomized teacher-led intervention to support executive function and self-regulation - Anne Marie Kristensen; Steven P. Blurton; Signe Vangkilde (Frontiers in Psychology, 2025)
BackgroundThe top-down cognitive and emotional control skills known as Executive Function (EF) and Self-Regulation (SR) have a large impact on everyday life. As a schoolchild, you are expected to pay attention, wait your turn, follow instructions, solve academic problems and be creative while navigating the social space of peers and teachers. All these abilities draw on EF and SR. Research has pointed to curricular programs as a promising path to build capacity in schoolteachers and provide with further knowledge on ways to support and strengthen these EF and SR skills in their pupils through activities, strategies and reflection tasks. The importance of EF and SR on later life outcomes such as academic performance, career, relationships and risk of crime, has been a motivating factor to develop the 10-session On Track 2.0 intervention as a universal whole-class approach to improve EF and SR in primary school pupils.MethodsRegular 4th and 5th grade class groups will be invited to participate in this teacher-delivered intervention program to be implemented into regular lessons. In this study schools will be randomly assigned to either intervention or control group as part of a cluster-randomized controlled trial. Psychometric and questionnaire assessing EF, SR and well-being will be administered to children, teachers and parents at three time points.DiscussionThe intervention holds the potential to support and qualify teachers in understanding students’ challenges with EF and SR better and in training these skills during class. A multimodal and multi-informant approach to assessment, in addition to data on teacher adherence and platform use, will aid the insight into the efficacy of the intervention content and delivery.Trial registrationThe study has been registered at Open Science Framework on 22 January 2025.